IMPLEMENTASI GERAKAN LITERASI SEKOLAH DI SMP MUHAMMADIYAH 2 SINGARAJA - jasmine, dila (ACARYA PUSTAKA, 2024)
Abstract This research aims to (1) determine the perceptions of Muhammadiyah 2 Singaraja Middle School students towards the Muhamadiyah 2 Singaraja Middle School Library. (2) To find out the perceptions of SMA Negeri 4 Singaraja students regarding the ideal school library. The research method used is a qualitative descriptive research method with informant collection techniques using purposive sampling. This research took place at the Muhammadiyah 2 Singaraja Middle School Library. Data collection in this research used observation, interview and document study techniques. The results of this research are that the majority of Muhammadiyah 2 Singaraja Middle School students have a good perception of the Muhammadiyah 2 Singaraja Middle School library. According to them, the Muhammadiyah 2 Singaraja Middle School library has an incomplete collection, but the novel collection is less diverse, the library space is less strategic and comfortable, the services and librarians are friendly. Apart from that, the majority of students at SMP Muhammadiyah 2 Singaraja have a perception that the school library is less than ideal, namely a library that lacks complete and varied collections with rooms that are less strategic and comfortable, which are managed by friendly and professional management staff so that they can provide maximum service to his students.